ANTICHOLINERGIC BURDEN IN AGING PATIENTS AND ITS ROLE IN THE DEVELOPMENT OF BLADDER DECOMPENSATION - Pustovoit, G.L.; Sarychev, L.P.; Savchenko, R.B.; Sarychev, Y.V.; Ustenko, R.L.; Sukhomlin, S.A. (World of Medicine and Biology, 2022)
Anticholinergic load is considered as a cumulative effect of medicine with anticholinergic activity. The article presents data of the role of anticholinergic load in the development of bladder decompensation in patients with benign prostatic hyperplasia. 381 patients with benign prostatic hyperplasia in the stage of subcompensation and decompensation of the bladder were examined. Anticholinergic load in elderly patients can develop both as a result of taking drugs with high potential anticholinergic activity and as a result of long-term use of drugs with low potential anticholinergic activity. Medicine with high potential anticholinergic activity reduce the symptoms of overactive bladder in patients with benign prostatic hyperplasia, but anticholinergic load becomes a deepening factor in the decompensation of bladder, which worsens the results of surgical treatment.